Exercise capacity of male and female national team athletes in canoe slalom - Sitkowski, Dariusz; Starczewski, Michał; Pokrywka, Andrzej; Żmijewski, Piotr; Opaszowski, Benedykt; Klusiewicz, Andrzej (Frontiers in Physiology, 2025)
IntroductionCanoe slalom is a well-established Olympic discipline. However, scientific knowledge regarding the physiological characteristics and training adaptations of its athletes, particularly among females, remains limited. To better characterize their exercise capacity, we retrospectively analyzed exercise test results collected over the past 20 years in our laboratory from both male (n = 110) and female (n = 43) national team members.MethodsFrom a total of 1,221 upper-body Wingate-type anaerobic test (30AOT) results and 908 graded exercise test (GXT) results performed on a kayak/canoe ergometer, only each athlete’s best performance was selected to reflect their maximal physiological capacity. This approach yielded 144 and 122 results for the 30AOT and GXT, respectively.ResultsIn all canoe slalom categories (Canoe Men, Canoe Women, Kayak Men, and Kayak Women), total work and peak power (W/kg) in the 30AOT were significantly higher in seniors than in juniors (p < 0.001–0.040). In the GXT, similar differences in power at the lactate threshold (LT) were observed (p < 0.001–0.028), except in Canoe Women. No significant differences in 30AOT results were found between canoeists and kayakers within corresponding age groups, nor in lactate concentration at the LT across all slalom categories, including both juniors and seniors. However, intergroup variation in heart rate at the LT was observed (p < 0.001), with canoeists showing significantly lower values than kayakers in the corresponding groups (p < 0.001–0.023).ConclusionThese results indicate that regular training in canoe slalom contributes to the development of both anaerobic and aerobic exercise capacities in male and female athletes. Additionally, no differences in anaerobic capacity were observed between canoeists and kayakers within the same age and sex categories. The potential influence of sport-specific selection and biological development—particularly in men—cannot be ruled out. Whether the lower HR at the LT in canoeists compared to kayakers results from reduced blood flow associated with the kneeling position warrants further investigation.